Low-velocity resistance distortion and bionic drag reduction for ship-type paddy field machinery - Yan, Guoqi; Tian, Peng; Mo, Jiasi; Xie, Heng; Wei, Huiling (International Journal of Agricultural and Biological Engineering, 2020)
The resistance between mud surface and ship-type paddy field machine hull accounts for a certain proportion of the total mechanical power consumption during the operation process. The special characteristic has been found via preliminary study, it showed that when starting or working at low velocity, the resistance is much greater than the machine working at the rated velocity. This characteristic affects the dynamic matching and structural design of the machine. The critical velocity of resistance distortion was around 0.025 m/s under the setting experimental conditions, and the mechanism of resistance distortion under multi-medium was analyzed. Based on water film drag reduction theory, a macroscopic structure of crocodile's abdominal armor biomimetic drag reduction method was proposed. Two kinds of bionic macroscopic structure ship board were fabricated. The macroscopic structure can introduce more water into the bottom surface of the hull; thicken the water film, which can reduce the travel resistance. Design and manufacture a ship-type paddy field experimental setup with velocity control, and compare the traditional smooth surface ship board with the two bionic macroscopic structure surfaces through orthogonal test. The experiment results demonstrated that the ship board with rectangle gully structure has better drag reduction effect than the hexagon one in the lower velocity. But when the travel velocity approach to the resistance distortion critical point, the hexagon gully structure become better than the other one. Through the orthogonal test, the best drag reduction combination is 2.5 kg load weight, 0.025 m/s travel velocity with hexagon ship board, which decreases the drag by 6.3%.Keywords: ship-type paddy field machinery, low velocity, resistance distortion, bionic, drag reduction, crocodileDOI: 10.25165/j.ijabe.20201302.5417Citation: Yan G Q, Tian P, Mo J S, Xie H, Wei H L. Low-velocity resistance distortion and bionic drag reduction for ship-type paddy field machinery. Int J Agric & Biol Eng, 2020; 13(2): 7–14.